Alciporin, a pore-forming protein as complementary defense mechanism in Millepora alcicornis - Nocchi, Nathalia; González-Orive, Alejandro; Hernández-Creus, Alberto; Lorenzo-Morales, Jacob; Rodríguez, Adriana; Morchón, Rodrigo; Díaz-Marrero, Ana R.; Fernández, José J. (Frontiers in Marine Science, 2022)
Millepora alcicornis (Cnidaria: Hydrozoa), known as fire coral, is a tropical species settled in marine ecosystems of the Canary Islands in the last years. This hydrocoral biosynthesizes toxins involved in chemical defense and prey capture mechanisms. Toxicological studies have shown that the venom contained in the nematocysts of Millepora species is mainly composed of thermolabile proteins that display hemolytic activity, causing skin irritation and burn-like lesions upon contact. As a continuation of a previous study, the chromatographic fractionation of the aqueous extracts of M. alcicornis has confirmed the coexistence of proteins of different nature responsible for the hemolytic effects of red blood cells (RBCs) through two different mechanisms. Aside from the already described phospholipase A2 (PLA2) activity, in this work the presence of alciporin, a pore-forming protein (PFP), has been established for the first time for M. alcicornis. The sequence analysis revealed that alciporin fit an actinoporin with high homology to stichotoxins. The hemolytic effects of alciporin were analyzed and sphingomyelin was identified as its biological target. Also, the evolution of the hemolytic damage produced at the nanoscale have been studied using atomic force microscopy (AFM).